Public Service Communication of Trans Metro Deli as a Commuter Transportation: A Study on UINSU Students - Rinaldi, Amanda Dita; Syahminan, Muhammad (CV. ITTC INDONESIA, 2024)
The purpose of this research is to explain and analyze public service communication applied by Trans Metro Deli to users, especially commuter students of the State Islamic University of North Sumatra. With the research method used by researchers in this study is a qualitative method with a descriptive approach. And for data collection using methods by means of interviews, observation and documentation. The results of this study indicate that Trans Metro Deli implements various communication strategies to improve services to users. These include establishing open and transparent communication by providing accurate and up-todate information to users, responding quickly and effectively to complaints and feedback from user. This research is expected to make an important contribution in understanding how public service communication is implemented.